Executive Committee Minutes 2011-02-03 - Academic Senate:::::::::
Resolution on Creating a Diversity Stakeholder's Exploratory Committee approved for Senate agenda. Revisions to the RTP policy approved for the Senate agenda. One faculty member for emeritus status approved for Senate consent calendar. From EPC: Request to revive the University Program Review subcommittee referred to Structure and Functions. By-Laws: Change to Article III, Section 2 – Representative Proxies approved for Senate agenda. Faculty Governance Reassigned time for '11 – '12 approved.